Imaging Recommendations for Molecular Imaging - Shaikh, Sikandar (Indian Journal of Medical and Paediatric Oncology, 2023)
In vivo molecular imaging is having a great potential that will have an impact on the medicine by detecting diseases in early stages like screening, identifying extent of disease, selecting disease- and patient-specific therapeutic treatment which will be the hallmark of the personalized medicine, for directed targeted therapy, and also for measuring molecular-specific effects of treatment. Currently, most commonly used molecular modalities are positron emission tomography- or single-photon emission computed tomography-based techniques.
Keywords: molecular imaging